A Novel Application of Virtual Reality for Pain Control: Virtual Reality-Mirror Visual Feedback Therapy - Sato, Kenji; Fukumori, Satoshi; Miyake, Kantaro; Obata, Daniel; Gofuku, Akio; Morita, Kiyoshi (IntechOpen, 2012)
None